Avaliação de fotorreatores na degradação de corantes reativos e efluente têxtil - Frank, Carla da Silveira (2004)
The continuous search for better quality of life, nowadays, implies in industrial growth e, consequently, in greater or minor degree of environmental pollution. The textile industry is responsible for part of this pollution; among the several environmental problems generated by the textile industry, two are distinguished: the not setting of dyes on the fibers, with losses of up to 50% of reactive dyes, and the great water consumption during the textile manufacturing (mean average of 100 L per kg of textile). The photocatalytic treatment of the reactive dyes (reactive red 4 and reactive blue 2) and the textile effluent was carried through by three different photo reactors: stirred tank and helicoidal tube photo reactors, both provided with TiO2 suspension; and rotative discs photo reactor, using immobilized TiO2. The parameters for the evaluation of the treatment efficiency were chemical oxygen demand (COD), absorptiometric color reduction and acute toxicity tests with bio indicators. Factorial planning was applied for the obtainance of the best results in terms of COD abatement of the effluent, and it was observed that the pH was the variable of greater importance for the applied processes. For the effluent treatment, in 120 min, the best results were obtained in stirred tank (pH 2, 500 mg TiO2, 60 °C and mercury vapor lamp) and helicoidal tube (pH 2, 200 mg TiO2, 50 °C, recirculation rate of 5 L h-1 and mercury vapor lamp) photo reactors, getting a COD abatement of 41% in both photo reactors, after factorial planning optimization. In the rotative discs photo reactor, by 16 rpm, xenon lamp and pH 2, a COD reduction of 36% was obtained, in 120 min. The photo catalysis performance in stirred tank photo reactor (pH 3, 400 mg of TiO2, 50 °C, mercury vapor lamp and dye concentration of 25 mg L-1), for the treatment of reactive red 4 and reactive blue 2 dyes, was enough for complete color removal in 5 and 10 min, respectively. The decolorization of the reactive red 4 and reactive blue 2 dyes, in helicoidal tube photo reactor, was possible in 20 and 40 min, respectively, by the following experimental conditions: pH 3, dye concentration of 25 mg L-1, 200 mg of TiO2, 50 °C and mercury vapor lamp. In the photo catalytic treatment using rotative discs photo reactor (pH 2, xenon lamp, 30 °C and velocity of 16 rpm), the solution of reactive red 4 was bleached in 120 min of treatment, and 150 min treatment was necessary for the decolorization of the reactive blue 2 solution.